Design issues in building Web-based parallel programming environments - Dincer, K.; Fox, G.C. (High-Performance Distributed Computing, 6th International Symposium on (Hpdc-6, 1997)
We exploited the recent advances in Internet connectivity and Web technologies for building Web-based parallel programming environments (WPPEs) that facilitate the development and execution of parallel programs on remote high-performance computers. A Web browser running on the user's machine provides a user-friendly interface to server-site user accounts and allows the use of parallel computing platforms and software in a convenient manner. The user may create, edit, and execute files through this Web browser interface. This new Web-based client-server architecture has the potential of being used as a future front-end to high-performance computer systems. We discuss the design and implementation of several prototype WPPEs that are currently in use at the Northeast Parallel Architectures Center and the Cornell Theory Center. These initial prototypes support high-level parallel programming with Fortran 90 and High Performance Fortran (HPF), as well as explicit low-level programming with Message Passing Interface (MPI). We detail the lessons learned during the development process and outline the tradeoffs of various design choices in the realization of the design. We especially concentrate on providing server-site user accounts, mechanisms to access those accounts through the Web, and the Web-related system security issues.